Evaluation of heavy metal content in jambu cultivation (Acmella oleracea [(L) R. K Jasen]) wiTH sediment of Tambaqui nursery (Colossoma macropomum) (Research, Society and Development, 2020)
Aquaculture has been highlighted in recent years as a source of animal protein, however, one of its obstacles is the improper disposal of its effluents, which in addition to having organic waste, has essential nutrients. And the reuse of these tailings in agriculture may be a likely way to remedy this problem, generating nutritious input to plants and mitigating environmental contamination. The study aimed to evaluate the viability of using fish pond sediment for the cultivation of jambu in the Amazon region. The experiment was conducted in a greenhouse at the Federal Rural University of Amazonia using waste from fish ponds. It consisted of five treatments, varying the concentrations of  anthropogenic dark earth (ADE) and sediment of fish pond (SFP), and conditioned with 1kg burned rice husk (BRH) for each concentration. The concentrations were composed of 100% TP, 25% SP + 75% TP, 50% SP + 50% TP, 75% SP + 25% TP and 100% SP. The sediment was collected in a semi-intensive tambaqui nursery in the municipality of Santa Isabel do Pará-PA and Jambu plants were irrigated daily up to 79 days after germination for harvesting. The experimental design was completely randomized with 5 treatments and 10 repetitions, one plant per repetition. Height (H), Collet diameter (D), Leaf number (LN), Chlorophyll (C), Leaf area (LA), Total fresh mass (TFM), Fresh leaf mass (FLM), Fresh Stem Mass (FSM), Fresh Flower Mass (FFM), Fresh Root Mass (FRM), Total Dry Mass (TDM), Dry Leaf Mass (DLM), Stem Dry Mass (SDM), Flower dry mass (FDM) and Root dry mass (RDM). Data were subjected to analysis of variance, and the equations were chosen based on the significance of the regression coefficients, at 5% probability, using the Sisvar software, version 5.6. Treatments 2 and 4 presented the highest values for most of the analyzed factors. Positive correlation was also found with sediment concentrations for H, LN, LA, FFM and FDM, when the linear regression behavior was analyzed, and the other parameters presented quadratic behavior, with optimal range always close to treatments 3 and 4. The production jambu with fish culture residues is feasible given the higher biomass increase in plants submitted to this type of substrate.